Consumers response to different certifications in social enterprises : the mediating role of brand credibility - Paiva, Catarina Santos (2021)
The objective of this dissertation is to understand the impact of certification type (awarded certification - symbolic certification) on consumer response, namely perceived trustworthiness and perceived expertise, taking into consideration the mediating role of brand credibility. An online survey containing a between-group factorial experiment design was used to test our hypothesis on a convenience sample of Portuguese consumers using a high-involvement product. Data was analysed through independent samples t-tests and the SPSS PROCESS macro to test for mediation. The findings displayed that, mediated by brand credibility, consumer response was higher for the awarded certification scenario. This study contributes to theory as it expands scientific knowledge in the field of social entrepreneurship along with consumer behaviour and marketing theories. While introducing a refresh view on certifications and their differences, proving that consumers perceive certifications types differently. Title: Consumers response to different certifications in social enterprises – the mediating role of brand credibility